Preparation method and application of a double-polymer high-voltage electrolyte
Patent Information
- Application Number
- CN202411430023.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-10-14
AI Technical Summary
[0003]本发明的目的是要解决现有水系电解质存在毒性,安全性差,不环保,高压稳定性差和耐低温性能的问题,而提供一种双聚合物高压电解质的制备方法和应用
[0011] I. The dual-polymer high-voltage electrolyte prepared in this invention is used in activated carbon//activated carbon (AC//AC) symmetrical supercapacitors. Test results show that it can operate stably within a voltage window up to 3V, and at 2Ag... -1 At a current density of [value missing], the first-cycle discharge capacity can reach 31.3 Fg. -1 After 500 cycles, the remaining capacity is 11.3 Fg. -1 The SC assembled from 2m LiTFSI in H2O has a maximum operating voltage of 2.4V, and its first-cycle capacity and 500-cycle capacity are only 24Fg. -1 and 2.4Fg -1 Furthermore, SCs assembled with 2m LiTFSIin P60PD30H10 electrolyte can achieve a pH of 1–5 Ag. -1 The discharge capacity of the SC assembly with 2mLiTFSI in H2O is maintained at approximately twice that of the SC assembly at a current density of [missing information]. This demonstrates that the dual polymer high-voltage electrolyte for supercapacitors provided by this invention has superior electrochemical performance.
Smart Images

Figure CN119314810B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing an aqueous electrolyte and its application. Background Technology
[0002] With the increasing global energy demand and the growing severity of environmental problems, the development of new, efficient, and environmentally friendly energy storage technologies has become particularly important. Compared with mainstream electrochemical energy storage technologies (lithium-ion batteries), aqueous energy storage devices (such as nickel-zinc batteries and nickel-metal hydride batteries) have advantages such as low cost, environmental friendliness, high power density, and good safety, and are expected to replace lithium-ion batteries in applications such as low- and mid-range electric vehicles and distributed energy storage. However, due to the poor thermodynamic stability of water, the electrochemical stability window of aqueous electrolytes cannot reach above 1.8V, making it difficult to match high-voltage, high-capacity electrode materials, resulting in the specific energy density of aqueous energy storage technologies being unable to effectively compete with lithium-ion batteries. Currently, methods to improve the electrochemical stability window of electrolytes mainly include high-concentration salts (salt-encapsulated water), the use of organic solvents, and the introduction of organic additives. While these methods can improve the electrochemical stability window of electrolytes to some extent, they also bring about several times the increase in cost and problems related to toxicity, safety, and environmental protection. Against this background, this invention successfully developed a dual-polymer molecular crowding aqueous high-voltage electrolyte and provided a method for preparing the above electrolyte, and verified its high-voltage stability using a supercapacitor as a model device. Summary of the Invention
[0003] The purpose of this invention is to solve the problems of toxicity, poor safety, environmental unfriendliness, poor high-pressure stability and low-temperature resistance of existing aqueous electrolytes, and to provide a method for preparing and applying a dual polymer high-pressure electrolyte.
[0004] A method for preparing a dual-polymer high-voltage electrolyte is specifically carried out according to the following steps:
[0005] 1. Mix polyethylene glycol, polyethylene glycol dimethyl ether and water, and stir until homogeneous to obtain an aqueous dipolymer molecular crowding solvent;
[0006] 2. Add lithium bis(trifluoromethanesulfonylimide) to an aqueous dual-polymer molecular crowding solvent and stir for a period of time to obtain a dual-polymer high-pressure electrolyte.
[0007] Application of a dual polymer high-voltage electrolyte in activated carbon / / activated carbon symmetric supercapacitors.
[0008] The principle of this invention:
[0009] This invention innovatively constructs a water-based dual-polymer molecular crowding solvent of polyethylene glycol (PEG) / polyethylene glycol dimethyl ether (PEGDME) / H2O, using lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as the lithium salt. PEG and PEGDME, as macromolecular polymers, contain numerous ethoxy, amino, and ether functional groups, which can form hydrogen bonds with water, binding water molecules and thus reducing the amount of free water and lowering water activity. This reduces the tendency for electrolysis (such as hydrogen evolution and oxygen evolution) at high voltages, expanding the electrochemical stability window of the electrolyte. Furthermore, the addition of LiTFSI, an electrolyte salt with similarly high electrochemical stability and environmental friendliness, results in an aqueous electrolyte with a high electrochemical stability window (3.64V) and high ionic conductivity, while also exhibiting extremely low cost, safety, and environmental friendliness. This significantly improves the performance of aqueous electrolytes at high voltages, broadens their application range, and provides a powerful reference for the design of high-voltage aqueous electrolytes.
[0010] Advantages of this invention:
[0011] I. The dual-polymer high-voltage electrolyte prepared in this invention is used in activated carbon / / activated carbon (AC / / AC) symmetrical supercapacitors. Test results show that it can operate stably within a voltage window up to 3V, and at 2Ag... -1 At a current density of [value missing], the first-cycle discharge capacity can reach 31.3 Fg. -1 After 500 cycles, the remaining capacity is 11.3 Fg. -1 The SC assembled from 2m LiTFSI in H2O has a maximum operating voltage of 2.4V, and its first-cycle capacity and 500-cycle capacity are only 24Fg. -1 and 2.4Fg -1 Furthermore, SCs assembled with 2m LiTFSIin P60PD30H10 electrolyte can achieve a pH of 1–5 Ag. -1 The discharge capacity of the SC assembly with 2mLiTFSI in H2O is maintained at approximately twice that of the SC assembly at a current density of [missing information]. This demonstrates that the dual polymer high-voltage electrolyte for supercapacitors provided by this invention has superior electrochemical performance.
[0012] II. The significance of this invention lies in its innovative use of the dual polymer molecular crowding effect, which not only effectively improves the electrochemical stability window of the electrolyte but also enhances energy density and cycle life, providing new possibilities for improving the performance of aqueous supercapacitors. It not only solves the problem of easy decomposition of aqueous electrolytes under high voltage but also avoids the significant cost increases and toxicity, safety, and environmental problems associated with using high-concentration salts and organic solvents. Furthermore, the environmental friendliness and cost-effectiveness of this electrolyte make it widely applicable in large-scale energy storage and electric vehicles. With the increasing global demand for sustainable energy technologies, the dual polymer molecular crowding aqueous high-voltage electrolyte of this invention is expected to become one of the key technologies driving the development of related industries. Attached Figure Description
[0013] Figure 1 Raman spectra of the two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared in Example 1 and Comparative Example 1 respectively;
[0014] Figure 2 A comparison of the electrochemical stability windows of two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared for LSV testing in Example 1 and Comparative Example 1.
[0015] Figure 3 Comparison of electrochemical impedance spectroscopy results for two electrolytes prepared in Example 1 and Comparative Example 1: 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O.
[0016] Figure 4 To test the symmetric supercapacitors assembled using two electrolytes prepared in Example 1 and Comparative Example 1, namely 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, respectively, at 1Ag... -1 Current density, comparison of constant current charge and discharge tests under different voltage windows;
[0017] Figure 5 To test the symmetric supercapacitors assembled using two electrolytes prepared in Example 1 and Comparative Example 1, namely 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, respectively, at 1Ag... -1 ~5Ag -1 The graph shows the rate performance test results at current density. In the graph, a represents 2m LiTFSI in H2O, and b represents 2m LiTFSI in P60PD30H10.
[0018] Figure 6To test the symmetric supercapacitors assembled using the two electrolytes prepared in Example 1 and Comparative Example 1, namely 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, respectively, at a current density of 2Ag... -1 Cyclic stability test results under the specified conditions;
[0019] Figure 7 A comparison of the electrochemical stability windows of electrolytes with different PEG to water ratios for LSV testing;
[0020] Figure 8 A comparison of the electrochemical stability windows of electrolytes with 60% PEG and 30% different types of second solvents when LSV testing was performed. Detailed Implementation
[0021] Specific Implementation Method 1: This implementation method provides a method for preparing a dual-polymer high-voltage electrolyte, which is specifically completed according to the following steps:
[0022] 1. Mix polyethylene glycol, polyethylene glycol dimethyl ether and water, and stir until homogeneous to obtain an aqueous dipolymer molecular crowding solvent;
[0023] 2. Add lithium bis(trifluoromethanesulfonylimide) to an aqueous dual-polymer molecular crowding solvent and stir for a period of time to obtain a dual-polymer high-pressure electrolyte.
[0024] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the number average molecular weight of the polyethylene glycol mentioned in step one is 200. The other steps are the same as in Specific Implementation Method One.
[0025] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 1 or 2 in that the mass fraction of polyethylene glycol in the aqueous dual polymer molecular crowding solvent described in step 1 is 50% to 70%. The other steps are the same as in Specific Implementation Method 1 or 2.
[0026] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the mass fraction of polyethylene glycol dimethyl ether in the aqueous dual polymer molecular crowding solvent described in step one is 20% to 40%. The other steps are the same as in Specific Implementation Methods One to Three.
[0027] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the mass fraction of water in the aqueous dual polymer molecular crowding solvent described in step one is 5% to 15%. The other steps are the same as in Specific Implementation Methods One to Four.
[0028] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the concentration of lithium bis(trifluoromethanesulfonylimide) in the dual polymer high-voltage electrolyte described in step two is 1.5 mol / kg to 2.5 mol / kg. The other steps are the same as in Specific Implementation Methods One to Five.
[0029] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the stirring speed in step two is 100 r / min to 1000 r / min, and the stirring time is 1 h to 2 h. The other steps are the same as in Specific Implementation Methods One to Six.
[0030] Specific Implementation Method 8: This implementation method is an application of a dual polymer high-voltage electrolyte in an activated carbon / / activated carbon symmetrical supercapacitor.
[0031] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One through Eight in that the preparation method of the activated carbon / / activated carbon symmetrical supercapacitor is specifically completed according to the following steps:
[0032] I. Preparation of activated carbon electrodes:
[0033] Activated carbon, conductive carbon black, and polyvinylidene fluoride are mixed evenly and ground to obtain a mixed electrode powder. N-methylpyrrolidone is added to the mixed electrode powder at a stirring speed of 150 r / min to 200 r / min, mixed evenly, and stirred for a period of time to obtain AC electrode slurry. The AC electrode slurry is evenly coated on aluminum foil and then dried to obtain an activated carbon electrode.
[0034] II. Assembling activated carbon / / Activated carbon symmetric supercapacitors:
[0035] The positive electrode battery casing, positive electrode sheet, glass fiber separator, negative electrode sheet, gasket, spring sheet, and negative electrode battery casing are stacked in that order. The dual polymer high-voltage electrolyte is dropped onto one side of the glass fiber separator. After being sealed by a button cell sealing machine, a supercapacitor is obtained.
[0036] The positive electrode sheet mentioned in step two is the activated carbon electrode prepared in step one;
[0037] The negative electrode sheet mentioned in step two is the activated carbon electrode prepared in step one. The other steps are the same as in specific embodiments one through eight.
[0038] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in the following ways: the activated carbon in step one is YP-80F; the mass ratio of activated carbon, conductive carbon black, and polyvinylidene fluoride in step one is 8:1:1; the grinding time in step one is 1 to 2 hours; the volume ratio of N-methylpyrrolidone to activated carbon in step one is 3 mL: 0.4 g; the stirring speed in step one is 200 r / min to 800 r / min, and the stirring time is 4 to 6 hours; the drying temperature in step one is 70°C to 90°C, and the drying time is 10 to 12 hours. Other steps are the same as in Specific Implementation Methods One to Nine.
[0039] The beneficial effects of the present invention are verified using the following embodiments:
[0040] Example 1: A method for preparing a dual-polymer high-voltage electrolyte, specifically carried out according to the following steps:
[0041] 1. Mix 3g of polyethylene glycol (PEG), 1.5g of polyethylene glycol dimethyl ether (PEGDME) and 0.5g of water, and stir until homogeneous to obtain an aqueous dual polymer molecular crowding solvent.
[0042] The number-average molecular weight of the polyethylene glycol mentioned in step one is 200;
[0043] In step one, the aqueous dual-polymer molecular crowding solvent contains 60% polyethylene glycol, 30% polyethylene glycol dimethyl ether, and 10% water by mass.
[0044] 2. Add 0.01 mol of lithium bis(trifluoromethanesulfonylimide) to an aqueous dual-polymer molecular crowding solvent and stir at 450 r / min for 1 h to obtain a dual-polymer high-voltage electrolyte (2 m LiTFSI in P60PD30H10).
[0045] Application Example 1: The assembly of an activated carbon / / activated carbon symmetric supercapacitor (SC) using the 2m LiTFSI in P60PD30H10 electrolyte prepared in Example 1 was carried out according to the following steps:
[0046] 1. Mix 0.4g activated carbon (YP-80), 0.05g conductive carbon black (Super P), and 0.05g polyvinylidene fluoride (PVDF) evenly and grind for 1 hour to obtain a mixed electrode powder. Add 3mL of N-methylpyrrolidone to the mixed electrode powder while stirring at 200r / min, mix evenly, and then stir at 500r / min for 5 hours to obtain an AC electrode slurry. Coat the AC electrode slurry evenly on an aluminum foil and dry at 80℃ for 12 hours to obtain an activated carbon electrode.
[0047] II. Assembling activated carbon / / Activated carbon symmetric supercapacitors:
[0048] The positive electrode battery casing, positive electrode sheet, glass fiber separator, negative electrode sheet, gasket, spring sheet, and negative electrode battery casing are stacked in that order. 0.4 mL of 2 mL LiTFSI in P60PD30H10 electrolyte prepared in Example 1 is dropped onto one side of the glass fiber separator (19 mm in diameter). After sealing with a button cell sealing machine, a supercapacitor is obtained.
[0049] The positive electrode sheet mentioned in step two is the activated carbon electrode prepared in step one;
[0050] The negative electrode sheet mentioned in step two is the activated carbon electrode prepared in step one.
[0051] The preparation method of the comparative example 1:2m LiTFSI in H2O electrolyte was carried out according to the following steps:
[0052] 0.01 mol of lithium bis(trifluoromethanesulfonyl)imide was added to 5 g of water and stirred at 450 r / min for 1 h to obtain 2 m LiTFSI in H2O electrolyte.
[0053] Comparative Application Example 1: Assembly of Activated Carbon / / Activated Carbon Symmetric Supercapacitor (SC) using 2m LiTFSI in H2O electrolyte prepared in Comparative Example 1 was carried out according to the following steps:
[0054] 1. Mix 0.4g activated carbon (YP-80), 0.05g conductive carbon black (Super P), and 0.05g polyvinylidene fluoride (PVDF) evenly and grind for 1 hour to obtain a mixed electrode powder. Add 3mL of N-methylpyrrolidone to the mixed electrode powder while stirring at 200r / min, mix evenly, and then stir at 500r / min for 5 hours to obtain an AC electrode slurry. Coat the AC electrode slurry evenly on an aluminum foil and dry at 80℃ for 12 hours to obtain an activated carbon electrode.
[0055] II. Assembling activated carbon / / Activated carbon symmetric supercapacitors:
[0056] The positive electrode battery casing, positive electrode sheet, glass fiber separator, negative electrode sheet, gasket, spring sheet, and negative electrode battery casing are stacked in that order. 0.4 mL of 2 mL LiTFSI in H2O electrolyte prepared in Comparative Example 1 is dropped onto one side of the glass fiber separator (19 mm in diameter). After sealing with a button cell sealing machine, a supercapacitor is obtained.
[0057] The positive electrode sheet mentioned in step two is the activated carbon electrode prepared in step one;
[0058] The negative electrode sheet mentioned in step two is the activated carbon electrode prepared in step one.
[0059] Figure 1 Raman spectra of the two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared in Example 1 and Comparative Example 1 respectively;
[0060] like Figure 1 As shown, the OH stretching vibration in 2m LiTFSI in H2O exhibits a relatively obvious broad peak, with a peak around 3200 cm⁻¹. -1 3400cm -1 3580cm -1 The peaks at these locations correspond to strong hydrogen, weak hydrogen, and non-hydrogen bond peaks, respectively. In a 2m LiTFSI inP60PD30H10 solvent, polymers PEG and PEGDME were added. The numerous ether oxygen atoms in the repeating structure of the polymer backbone have high electronegativity and can act as hydrogen bond acceptors, interacting with hydrogen bond donors in water molecules to form hydrogen bonds, thus binding water molecules. Simultaneously, PEG contains terminal hydroxyl groups (-OH), which can act as hydrogen bond donors, forming hydrogen bonds with oxygen atoms in water, further binding water molecules, reducing the content of free water, and further decreasing the activity of water. This corresponds to a decrease in the intensity of strong and weak hydrogen bond peaks in the Raman spectrum, while the intensity of non-hydrogen bond peaks increases, with a peak appearing at approximately 3830 cm⁻¹. -1 The peak at this point corresponds to the OH bond vibration of water molecules that are not bound by hydrogen bonds, indicating that in the electrolyte after adding PEG and PEGDME to the solvent, most water molecules exist in isolation or do not form hydrogen bonds with surrounding water molecules.
[0061] In a Swagelok cell, using an Ag / AgCl reference electrode and titanium foil as both the working and counter electrodes, linear sweep voltammetry (LSV) curves of 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O electrolytes were measured using a three-electrode setup on a CHI660E electrochemical workstation. The scan rate was 0.2 mV / s. -1 The voltage range is -2 to 3 (V vs. Ag / AgCl), and the electrochemical stability window of the two electrolytes is determined using a cutoff current of ±20 μA. For example... Figure 2 As shown;
[0062] Figure 2 A comparison of the electrochemical stability windows of two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared for LSV testing in Example 1 and Comparative Example 1.
[0063] from Figure 2It can be seen that the electrochemical stability window of 2m LiTFSI in P60PD30H10 electrolyte is 3.64V, while that of 2m LiTFSI in H2O electrolyte is only 2.0V. This indicates that using a dual polymer molecular crowding agent can significantly improve the electrochemical stability window of aqueous electrolytes.
[0064] To compare the ion transport performance of 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O electrolytes, a stainless steel / / stainless steel blocking battery was assembled, and the electrochemical impedance spectroscopy (EIS) of the two electrolytes was measured. Figure 3 As shown;
[0065] Figure 3 Comparison of electrochemical impedance spectroscopy results for two electrolytes prepared in Example 1 and Comparative Example 1: 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O.
[0066] from Figure 3 It can be seen that the 2m LiTFSI in P60PD30H10 electrolyte has the lowest electrochemical impedance and the highest ionic conductivity.
[0067] The actual operating voltage window of a supercapacitor is not only related to the electrolyte performance but may also be affected by multiple factors such as the type of electrode material. Therefore, the actual operating voltage window may not be exactly the same as the electrochemical stability window of the electrolyte. To further test the electrochemical performance and application potential of the 2m LiTFSI in P60PD30H10 electrolyte in this invention, the constant current charge-discharge curve (GCD) of the assembled AC / / AC symmetrical supercapacitor was tested to observe the actual operating voltage window of the symmetrical capacitor. Figure 4 As shown in Figure a, a symmetrical supercapacitor assembled with 2m LiTFSI in P60PD30H10 can operate at around 3V without electrolyte decomposition; simultaneously, as Figure 4 As shown in b, the GCD curve of the symmetrical supercapacitor assembled with 2m LiTFSI in H2O showed significant distortion when charged to about 2.2V, indicating that the electrolyte had decomposed. When charged to 2.7V, the curve was severely distorted, and the capacity reversibility also decreased significantly. Therefore, the actual operating voltage window of the device with this electrolyte is only about 2.2V.
[0068] A symmetrical supercapacitor assembled from 2m LiTFSI in H2O at 1Ag -1 ~5Ag -1 Rate performance testing at current density, such as Figure 5As shown in Figure a, a symmetrical supercapacitor assembled using two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, operates at 1Ag. -1 ~5Ag -1 Rate performance testing at current density, such as Figure 5 As shown in b. Calculations show that the discharge specific capacity of a symmetrical supercapacitor assembled with 2m LiTFSI in P60PD30H10 is approximately twice that of a symmetrical supercapacitor assembled with 2m LiTFSI in H2O at the same current density.
[0069] An AC / / AC symmetrical supercapacitor assembled from 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O operates at a current density of 2Ag. -1 Under these conditions, the capacity retention rate after 500 cycles is as follows: Figure 6 As shown, after 500 repeated charge-discharge cycles, the capacitor assembled with 2m LiTFSI in P60PD30H10 still retains 36% of its initial capacitance, while the capacitor assembled with 2m LiTFSI in H2O only retains 10% of its initial capacitance. This indicates that the 2m LiTFSI in P60PD30H10 electrolyte has superior cycle performance.
[0070] To determine the effect of different PEG content solvents on electrolyte performance, 2m LiTFSI solutions with varying ratios of PEG to water were prepared as electrolytes. The PEG mass fraction in the solvent ranged from 30% to 60%, and the water mass fraction ranged from 70% to 40%. To compare the electrochemical stability windows of the four electrolytes, linear sweep voltammetry (LSV) curves of these electrolytes were measured using a three-electrode setup in a Swagelok cell with an Ag / AgCl reference electrode and titanium foil as both the working and counter electrodes on a CHI660E electrochemical workstation. Figure 7 As shown, the electrolyte has the largest electrochemical stability window when the PEG content is 60%.
[0071] Additionally, 2 mL LiTFSI solutions with a PEG content of 60% were prepared, each containing 30% by mass of polyethylene glycol dimethyl ether (PD), acetonitrile (AN), methanol (JC), ethanol (YC), and ethylene glycol (EG) as solvents. The electrochemical stability windows of these five electrolytes were tested using the same method. Figure 8 As shown, the electrolyte using PEG60PD30H10 solvent has the widest electrochemical stability window, while electrolytes using other solvents all experience side reactions to varying degrees, resulting in a lower electrochemical stability window.
Claims
1. A method for preparing a dual-polymer high-voltage electrolyte, characterized in that... The preparation method is specifically carried out according to the following steps:
1. Mix polyethylene glycol, polyethylene glycol dimethyl ether and water, and stir until homogeneous to obtain an aqueous dipolymer molecular crowding solvent; In step one, the aqueous dual-polymer molecular crowding solvent contains 60% polyethylene glycol, 30% polyethylene glycol dimethyl ether, and 10% water by mass.
2. Add lithium bis(trifluoromethanesulfonylimide) to an aqueous dual-polymer molecular crowding solvent and stir for a period of time to obtain a dual-polymer high-pressure electrolyte. The concentration of lithium bis(trifluoromethanesulfonylimide) in the dual polymer high-voltage electrolyte described in step two is 1.5 mol / kg to 2.5 mol / kg.
2. The method for preparing a dual-polymer high-voltage electrolyte according to claim 1, characterized in that... The number-average molecular weight of the polyethylene glycol mentioned in step one is 200.
3. The method for preparing a dual-polymer high-voltage electrolyte according to claim 1, characterized in that... The stirring speed in step two is 100 r / min to 1000 r / min, and the stirring time is 1 h to 2 h.
4. The application of a dual-polymer high-voltage electrolyte prepared by the preparation method according to claim 1, characterized in that... Application of a dual polymer high-voltage electrolyte in activated carbon / / activated carbon symmetric supercapacitors.
5. The application of the dual polymer high-voltage electrolyte according to claim 4, characterized in that... The preparation method of the activated carbon / / activated carbon symmetrical supercapacitor is specifically carried out according to the following steps: I. Preparation of activated carbon electrodes: Activated carbon, conductive carbon black, and polyvinylidene fluoride are mixed evenly and ground to obtain a mixed electrode powder. N-methylpyrrolidone is added to the mixed electrode powder at a stirring speed of 150 r / min to 200 r / min, mixed evenly, and stirred for a period of time to obtain AC electrode slurry. The AC electrode slurry is evenly coated on aluminum foil and then dried to obtain an activated carbon electrode. II. Assembling activated carbon / / Activated carbon symmetric supercapacitors: The positive electrode battery casing, positive electrode sheet, glass fiber separator, negative electrode sheet, gasket, spring sheet, and negative electrode battery casing are stacked in that order. The dual polymer high-voltage electrolyte is dropped onto one side of the glass fiber separator. After being sealed by a button cell sealing machine, a supercapacitor is obtained. The positive electrode sheet mentioned in step two is the activated carbon electrode prepared in step one; The negative electrode sheet mentioned in step two is the activated carbon electrode prepared in step one.
6. The application of the dual polymer high-voltage electrolyte according to claim 5, characterized in that... The activated carbon mentioned in step one is YP-80F; the mass ratio of activated carbon, conductive carbon black, and polyvinylidene fluoride mentioned in step one is 8:1:1; the grinding time mentioned in step one is 1h~2h; the volume ratio of N-methylpyrrolidone to activated carbon mentioned in step one is 3mL:0.4g; the stirring speed mentioned in step one is 200r / min~800r / min, and the stirring time is 4h~6h; the drying temperature mentioned in step one is 70℃~90℃, and the drying time is 10h~12h.
Citation Information
Patent Citations
Bionic aqueous electrolyte, preparation method and application in supercapacitor
CN112053857A
Aqueous double-electric-layer supercapacitor electrolyte and preparation method and application thereof
CN117766304A